Design consideration of N-drift region doping concentration in high voltage VDMOS transistor - Haziezol Helmi bin Mohd Yusof, H.H.M.Yusof; Wijaya Bayu Murti, Wijaya Bayu Murti; Norhayati binti Soin, N.Soin (2014)
N-drift doping concentration has important contribution in determining the breakdown voltage and on-resistance of the device. It should be well considered because higher N- drift doping concentration can minimize the on-resistance of the device, but also lowering breakdown voltage of the device that expected to be high. It also has a proportional relationship with threshold voltage degradation caused by hot carrier injection. So the variation of N-drift doping concentration can be used to optimize the VDMOS transistor performance.